Public Use Management for National Protected Areas in Costa Rica: Literature Review, Synthesis, and Research Agenda - Mayorga Castro, Marisol (2024)
Public use management research illuminates how people use and experience the sites they visit, their possible impacts and mitigation, as well as how to design infrastructure and management strategies that better serve visitors while protecting heritage, facilities, ecological conditions, and surrounding communities. Despite increasing visitation to Costa Rican protected areas, it has been unclear how much research about public use management has occurred at these destinations. This study then presents a literature review and synthesis of the research from 119 publications (namely, peer reviewed articles, theses, reports, and books) related to public use management in Costa Rica. An Integral Theory-based framework was used to classify publications and visualize the nature, emphasis, and gaps of the research. As a result, an agenda was proposed to organize and maximize public use management research in national protected areas. Because of its integral approach, this agenda could also be applied to other public and private protected areas in Costa Rica and throughout Latin America.